2010
DOI: 10.1007/s00423-010-0696-0
|View full text |Cite
|
Sign up to set email alerts
|

Familial nonmedullary thyroid carcinoma—clinical relevance and prognosis. A European multicenter study

Abstract: FNMTC is associated with an early onset of small, mostly papillary thyroid carcinomas and an increased risk of multifocality and lymph node involvement. Total thyroidectomy and systematic neck dissection are recommended together with radioiodine ablation. Screening for first-degree relatives should start at age 18 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
5
28
0
1
Order By: Relevance
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussionsupporting
confidence: 73%
“…Although some studies have reported a less favourable prognosis for FNMTC (3,16,17,18,19,20,21), others did not verify this (1,22,23,24,25), and therefore, the biological and clinical behaviour of this familial disease, as compared with the much more frequent sporadic forms, remains a matter of controversy. Furthermore, data on molecular biomarkers, e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, based on the current available evidence, it may be rational that screening individuals with relatives affected by thyroid cancer commence at an earlier age. However, there is no strict age cutoff at which screening should begin; some authors (17,22,23) recommend that screening should commence at the age of 18-20 years, or 5-10 years earlier than the youngest age of diagnosis with the family, which remains to be further elucidated. As given in Table 2, most of subgroup analyses did not show significant difference to the overall conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have found that FNMTC has more aggressive biological behaviors, characterized by a higher incidence of multifocality, extrathyroidal invasion, bilateral disease, and lymph node metastases, which lead to a higher recurrence rate and decreased disease-free survival (DFS) (11,12,13,14,15,16,17). Therefore, some of them recommended more aggressive initial treatment for patients with FNMTC, including total thyroidectomy (TT) and concomitant prophylactic central compartment node dissection (14,17). However, certain other studies did not confirm the difference in biological behaviors between FNMTC and SNMTC (18,19,20,21).…”
Section: Introductionmentioning
confidence: 99%